2006
DOI: 10.1016/j.virol.2006.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Infection of CD4+ T lymphocytes by the human T cell leukemia virus type 1 is mediated by the glucose transporter GLUT-1: Evidence using antibodies specific to the receptor's large extracellular domain

Abstract: To analyze HTLV-1 cytotropism, we developed a highly sensitive vaccinia virus-based assay measuring activation of a reporter gene upon fusion of two distinct cell populations. We used this system in a functional cDNA screening to isolate and confirm that the glucose transporter protein 1 (GLUT-1) is a receptor for HTLV-1. GLUT-1 is a ubiquitously expressed plasma membrane glycoprotein with 12 transmembrane domains and 6 extracellular loops (ECL). We demonstrate for the first time that peptide antibodies (GLUT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Formation of a virological synapse, polarization of the cytoskeleton, and passage of HTLV-1 virions have been observed during contact between infected and noninfected T cells (5). Although the precise mechanism of HTLV-1 virion transfer remains elusive, several recent studies have suggested that the glucose transporter 1 (GLUT1) can function as a receptor for HTLV (2,13) as well as participate in Env-mediated cellcell fusion (2,7). However, it is still unclear whether GLUT1 is important for cell-to-cell transmission of HTLV-1.…”
Section: The Human T-cell Leukemia Virus Type I (Htlv-1) (19) Ismentioning
confidence: 99%
“…Formation of a virological synapse, polarization of the cytoskeleton, and passage of HTLV-1 virions have been observed during contact between infected and noninfected T cells (5). Although the precise mechanism of HTLV-1 virion transfer remains elusive, several recent studies have suggested that the glucose transporter 1 (GLUT1) can function as a receptor for HTLV (2,13) as well as participate in Env-mediated cellcell fusion (2,7). However, it is still unclear whether GLUT1 is important for cell-to-cell transmission of HTLV-1.…”
Section: The Human T-cell Leukemia Virus Type I (Htlv-1) (19) Ismentioning
confidence: 99%
“…HTLV-1 can be transmitted from mother to child, during sexual intercourse, and through contaminated blood products 7 . HTLV-1 has a special tropism for CD4+ lymphocytes and uses GLUT-1, the ubiquitous vertebrate glucose transporter, as the main receptor to infect cells 8 . It is trans-mitted from cell to cell through a viral synapse and enters target cells via interaction with GLUT-1 in association with Neuropilin-1 (NRP1), the receptor for semaphorin-3A, and VEGF-A165, a member of the immune synapse.…”
mentioning
confidence: 99%
“…GLUT1 binds to HTLV-1 and HTLV-2 envelope proteins, and GLUT1 depletion in target cells reduces infection by HTLV-2-enveloped pseudotypes (36). The overexpression of GLUT1 increases the susceptibility of resistant cells to HTLV-1 Env-mediated cell fusion and infection (9), and an antibody directed to GLUT1 blocks HTLV-1 Envmediated cell fusion and infection of primary CD4 ϩ T lymphocytes (23). Mutation of residue 106 or 114 of Env reduces or abolishes the interaction of SU with GLUT1 (36), account-ing for the importance in HTLV-1 Env functions of the amino acid 100 region of the SU.…”
mentioning
confidence: 99%